Geographic distribution of the Pygmy Squirrel Sciurillus pusillus (É. Geoffroy-St.-Hilaire, 1803) (Rodentia: Sciuridae) in the northwestern Amazonia, southern Colombia - María Calderón-Capote; Juan Díaz-Nieto; Hugo López-Arévalo (Check List, 2015)
We evaluated the occurrence of Sciurillus pusillus in Colombia and present the first confirmed records of the species in the country based on material deposited at Instituto de Investigación de Recursos Biológicos Alexander von Humboldt, Villa de Leyva (IAvH, former INDERENA). The mentioned material was collected in two localities from vicinities of town La Chorrera, Igara-Paraná River, Amazonas Department of Colombia. Additionally, we provide a description of the baculum from one of the specimens herein recorded from Colombia.